Biomass Productivity of Invasive Mantangan (Merremia peltata) under Various Canopy Covers - Duryat; Santori; Trio Santoso; Melya Riniarti; Rikha Aryanie Surya (Jurnal Sylva Lestari, 2023)
Mantangan (Merremia peltata) is the most important invasive species in Bukit Barisan Selatan National Park (BBSNP) due to its fast-growing and spreading that potentially damage and threat biodiversity conservation. The objectives of this study were to determine the biomass stock and productivity of mantangan and the nutrient content of mantangan biomass grown in various classes of canopy cover. Stratified sampling was employed as a sampling method on three classes of canopy cover, i.e., sparse (light intensity > 70%), medium (light intensity 40 -70%), and dense (light intensity < 40%). A destructive method was used to collect biomass samples. The biomass harvesting was conducted twice. The first was conducted to determine biomass storage and nutrient content, and the second was conducted a month later to measure biomass productivity. The macronutrient content (N, P, K, and C-Organic) of mantangan was analyzed at the Soil Science Laboratory, Faculty of Agriculture, University of Lampung. The results showed that the biomass stock and productivity differed in each canopy cover class. The highest biomass stock was found in sparse canopy cover (192 kg/ha), followed by medium (188 kg/ha) and dense (179 kg/ha). Biomass productivity was highest in sparse canopy cover (93 kg/ha/month), followed by medium (79 kg/ha/month) and dense (83 kg/ha/month), respectively. Surprisingly, the nutrient content and nutrient productivity of mantangan grown on medium canopy cover were higher than that of dense and sparse. Keywords: Biomass, Bukit Barisan Selatan National Park, invasive alien species, mantangan